How leader and follower prototypical and antitypical attributes influence ratings of transformational leadership in an extreme context - Avolio, Bruce J. (2021)
Leadership is a process where leaders enact certain behaviors to influence followers. Yet, each follower may view the leader’s enactment differently, owing to differences in disposition and context. Here we examine leadership as a property attributed by followers to their leader, influenced by both the leader and followers’ personal attributes and the situation in which leaders and followers interact. Guiding this study, we asked: how do followers’ affect (negative and positive traits), motivation (regulatory focus), and cognitions (identity) and their congruence with their leader’s corresponding attributes influence their ratings of transformational leadership? Participants operated in extreme situations where their lives were often at risk because of exposure to combat. Results based on a sample of 1587 US Army soldiers operating in 262 units show that when there is a higher congruence between leaders’ and followers’ positive affect, promotion focus, relational identity, and collective identity, follower ratings of transformational leadership are higher, whereas a higher level of incongruence between followers’ and leaders’ positive and negative affect predicted lower ratings of transformational leadership. These findings differed based on the soldiers’ time spent in deployment and the level of combat exposure they experienced.